مدى مساهمة الطاقة الشمسية كمورد اقتصادي مستدام في تحقيق التنمية بالجزائر - بن عبو, سنوسي (جامعة مسيلة, 2018)
Algeria is one of the most important Mediterranean countries, with its geographical location, vast expanses and diverse climate. It is the heart of the Arab Maghreb and the natural corridor between Europe and Africa, the country rich in natural resources such as mineral and animal wealth and resources. Among the revenues of the large sector, but it remains an economic resource is not safe and this is due to the possibility of access to the reserve in the coming years as well as low fuel prices for many periods can cause the The countries must adopt a strategy of diversification of energy sources and dependence on renewable and immortal resources and contribute to rationalizing the exploitation of fossil fuels and achieve sustainable development. Through this study, we seek to highlight the potential of Algeria in the field of solar energy after the interest of the renewable energy sector in the framework of applied development policy, which aims primarily to diversify the economy as an important factor for the security of energy supply in the medium and long term. And is necessary in light of insufficient fossil energy sources in addition to the role it plays in achieving sustainable development, where solar energy is the most efficient alternative in Algeria compared to other renewable energies because vast desert areas available Allow it to take advantage of the sun's rays in large quantities, in addition to the costs enjoyed by these renewable energy factors, which incites the authorities of the public interest in this kind of energy and the exploitation and encouraged by the launch of several important projects in this context. This is to build Algeria of tomorrow.
Keywords: fossil fuels; sustainable development; renewable energy; solar energy; projects Codes de classification de Jel : E2, Q56